Beyond Canine Adipose Tissue-Derived Mesenchymal Stem/Stromal Cells Transplantation: An Update on Their Secretome Characterization and Applications - Barbara Merlo; Eleonora Iacono (Animals, 2023)
A dog is a valuable animal model and concomitantly a pet for which advanced therapies are increasingly in demand. The characteristics of mesenchymal stem/stromal cells (MSCs) have made cell therapy more clinically attractive. During the last decade, research on the MSC therapeutic effectiveness has demonstrated that tissue regeneration is primarily mediated by paracrine factors, which are included under the name of secretome. Secretome is a mixture of soluble factors and a variety of extracellular vesicles. The use of secretome for therapeutic purposes could have some advantages compared to cell-based therapies, such as lower immunogenicity and easy manufacturing, manipulation, and storage. The conditioned medium and extracellular vesicles derived from MSCs have the potential to be employed as new treatments in veterinary medicine. This review provides an update on the state-of-the-art characterization and applications of canine adipose tissue-derived MSC secretome.